Assessment of spatial variability in physico- chemical properties of soils in Alirajpur district of Madhya Pradesh using Geo-statistical approach - YADAV, TIKAM CHAND; RAI, H. K.; CHAUBEY, DAYANIDHI; DHAKAD, R. (Journal of Soil and Water Conservation, 2018)
Information regarding spatial variability and distribution of soil properties is critical for stakeholders attempting to increase nutrients use efficiency and crop productivity. Application of fertilizers on the basis of soil characteristics maps associated with fertilizers recommendation may aid to curtail fertilizers inputs without surrendering the crop yield. The present study was focused on assessing the variability in physico-chemical properties of soils in Alirajpur district of Madhya Pradesh using geo-statistical approach. 272 GPS based surface (0-15 cm) soil samples were collected from six blocks (Alirajpur, Bhabra, Jobat, Kathiwara, Sondwa, and Udaigarh) of Alirajpur district after harvest of crops during rabi season 2016-17. Soils samples were processed and analyzed in the laboratory using standard procedures for different physico-chemical characteristics. The data obtained from laboratory analysis were statistically and geo-statistically interpreted. The results revealed that pH, EC, OC and CaCO3 of soils collected across different blocks of Alirajpur district varied from 4.70 to 8.40, 0.03 to 0.90 dSm-1, 0.47 to 12.92 g kg-1 and 5 to 115 g kg-1 soil, respectively. Whereas, available N, P, K and S in soils ranged from 76 to 382 kg ha-1, 1.34 to 62.13 kg ha-1, 253.52 to 529.85 kg ha-1 and 0.55 to 33.90 mg kg-1, respectively. The results obtained in the present study clearly showed a large variability in physico-chemical properties of soil across the Alirajpur district. This information could aid in decision making for application of plant nutrients and selection of cropping sequence for higher monetary returns to the farmers.